PARALELIZAÇÃO DE MÉTODOS COMPUTACIONAIS APLICADOS A VARIAÇÃO DE UMIDADE NO SOLO - PADOIN, EDSON L.; BORGES, PEDRO A. P.; DILL, SERGIO L.; BORGES, ROBERTO S.; RODRIGUES, ALESSANDRO; WIEST, ROBERTO (Salão do Conhecimento, 2013)
Resumo